Interpretation of Space Through Metaphors - Isfandiyar Gizi, Ahmadova Ramila (Advances in Social Sciences Research Journal, 2018)
The present paper aims to analyze the metaphorical representation of space from a cognitive point of view in the English language. To achieve this purpose it mostly focuses on the investigation of space metaphors. It also presents certain ways in which metaphoric expressions represent space. Different view points of the lingusits are stated throughout the paper. The author attempts a better understanding of metaphors in terms of expressing space. The paper is fully representative of the state of the art in terms of language and space research , and point to new directions in terms of findings, theory and practice. This article is to a large extent about how these and other unconscious spatial activities relate to language and how language relates to space. This is an area of enquiry that has interested linguits, philisophers , and psychologists for a very long time and for a variety of reasons. In recent years cognitively oriented linguits have devoted more and more research , effort into trying to comprehend the space – language relationship especially space metaphors. The present paper aims to give an overview of some aspects of this effort, its current state. Examples provided contribute to demonstarte that space metaphors constitutes an essential part of our conceptual system.